Implementasi Quranic Bibliotherapy untuk Menurunkan Kecemasan pada Ibu Hamil: Implementation of Quranic Bibliotherapy to Reduce Anxiety in Pregnant Mothers - Ariani Fatmawati; Popy Siti Aisyah; Inggriane Puspita Dewi; Resha Eka Febriyani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Health care for expectant women primarily focuses on physical health, particularly in Independent Midwife Practice (PMB) in Bandung. Currently, only blood pressure checks, weight assessments, the administration of iron supplements, laboratory testing, tetanus vaccinations, and assessments of the fetus's position and heart rate are performed. Meanwhile, stress or anxiety is every day during pregnancy for pregnant women. This condition needs to be treated, and one method is spiritual. Using Quranic bibliotherapy as spiritual intervention, anxiety during pregnancy is reduced. Pregnant women who experienced anxiety were given anxiety questionnaires to complete, and those who did were gathered into groups and given three meetings' worth of quranic bibliotherapy through Zoom. Pregnant women who reported experiencing anxiety were subsequently collected into groups and given a three-meeting Quranic bibliotherapy intervention through Zoom Meetings and in person. The activity began with the distribution of anxiety questionnaires to pregnant women. The activity's results revealed that there had been a change in the participants' levels of anxiety, which had previously ranged from mild anxiety at 40% to moderate anxiety at 50%, severe anxiety at 10%, mild anxiety at 60%, and moderate anxiety at 40%. To use quranic bibliotherapy interventions on anxious pregnant women, midwives must have the necessary training.